Longitudinal modeling of health-related quality of life trajectories over 12 months following road trauma - Somayeh Momenyan; Herbert Chan; Shannon Erdelyi; Lulu X. Pei; Lina Jae; John A. Taylor; John A. Staples; Jeffrey R. Brubacher (PLoS ONE, 2025)
Introduction This study identified the potential phases of health-related quality of life (HRQoL) change over a year following road trauma (RT) injury, as well as its predictors. Methods This inception cohort study recruited 1480 Canadian RT survivors from July 2018 to March 2020. HRQoL outcome was assessed with the 5-level version of the EuroQol (EQ-5D-5L) instrument at baseline (pre-injury) and at 2, 4, 6, and 12 months post-injury. Predictors of HRQoL included sociodemographic, psychological, medical, and trauma-related factors collected at baseline. We applied generalized additive mixed models to flexibly capture nonlinear changes in HRQoL over time, and piecewise latent growth curve model to analyze distinct linear phases of recovery across defined time intervals. Results The estimated trajectory of EQ-5D-5L summary and EQ-VAS scores were lower than baseline at 2-months (phase 1), and then increased (phase 2), but did not return to baseline values at 12-months. White ethnicity, higher somatic symptom, pain catastrophizing, and use of medication pre-injury were associated with lower pre-injury EQ-5D-5L summary and EQ-VAS scores. Phase 1 EQ-5D-5L decreases were associated with female sex, no pre-existing body complaints, lack of expectation for a fast recovery, higher ISS, higher injury pain, and neck, spine/back, upper extremity, or lower extremity injuries. Phase 1 EQ-VAS decreases were associated with female sex, lower somatic symptom, fewer comorbidities, lack of expectation for a fast recovery, higher ISS, higher injury pain, neck, spine/back or lower extremity injuries. In phase 2, EQ-5D-5L summary improved most in participants with higher education levels and longer recovery expectations; EQ-VAS improved most in cyclists and patients with longer recovery expectations. Conclusions Clinicians should assess and address patients’ recovery expectations early in the care process, as these may significantly influence long-term HRQoL outcomes. Incorporating strategies to support realistic yet positive expectations, such as cognitive-behavioral therapy, structured patient education, and goal-setting programs, may improve recovery experiences. In addition, identifying patients with high pain, or specific injury types may help target early interventions to those at risk of poor HRQoL trajectories.